Eipone Lo Edukunere Ka Ayait Aingadis Na Ikinyom. Itaabon Lu Ikakoriok. Eitaabo 3 Kotoma 3. Eyaitene, Arucokina, Ikisila Ka Nu Ebeit Atupit [Ateso version] - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon R.; Porcuna Ferrer, Anna (Bioversity International and the International Center for Tropical Agriculture, 2021)
Ateso version of How to develop and manage your own community seed bank: Farmers’ handbook (updated version). Management, networking, policies and a final checklist: Booklet 3 of 3. This handbook is a companion to Vernooy, R., Sthapit, B. and Bessette, G. (2020). Community seed banks: concept and practice. Facilitator handbook (updated version). Bioversity International, Rome, Italy (https://hdl.handle.net/10568/81286). The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Booklet 1 of 3 (Ateso) can be found here: https://hdl.handle.net/10568/113895. Booklet 2 of 3 (Ateso) can be found here: https://hdl.handle.net/10568/113897. Translation and adaptation to the local language is encouraged. If you would like to receive a hard copy of the booklets or give feedback or suggestions for improvement, please contact r.vernooy@cgiar.org.